Integrating wearable mobile health technologies into chronic heart failure management: Insights from a mixed-methods study and persona development - Svensson, Laura; Anders, Carolin; Dieterich, Christoph; Heinze, Oliver; Knaup-Gregori, Petra; Weinert, Lina (Digital health, 2025)
Background: Chronic heart failure (CHF) affects over 64 million people globally and often reduces quality of life (QoL), contributing to higher mortality. Wearable devices offer opportunities for continuous monitoring and self-management. However, patient characteristics and perceptions of wearables vary, and healthcare practitioners (HCPs) lack guidance on identifying patients who would benefit from such tools. This study investigates patients’ experiences with wearables for self-monitoring and develops personas to assist HCPs in tailoring CHF management. Methods: A mixed-methods approach was used, combining qualitative semi-structured interviews and quantitative QoL data via the Kansas City Cardiomyopathy Questionnaire (KCCQ-12). CHF patients received an Apple Watch and iPhone SE for tracking vital data and completing questionnaires and participated in semi-structured interviews. Descriptive analysis of KCCQ-12 scores and thematic analysis of interview transcripts informed the creation of patient personas based on previous findings. Results: Thematic analysis identified six main themes, including self-monitoring practices, barriers, and factors influencing acceptance. Most patients used wearables daily, reporting benefits like increased health awareness and improved communication with doctors. Barriers included technical issues and difficulty integrating study devices with personal ones. Quantitative analysis suggested a tendency toward higher QoL among interview participants. Four personas emerged, reflecting varying levels of motivation, literacy, and disease burden. Conclusion: Wearables show promise for improving CHF self-management by enhancing health awareness and providing reassurance. However, technical issues and integration challenges remain barriers. The developed personas offer HCPs a practical tool to personalize care and identify patients most likely to benefit from wearables.
Gesehen am 22.01.2026